International student mobility from Latin America in Australia: What we already know and what we still need to find out. Issue 1 (1st March 2020) - Paull, David
This article identifies five main mobility characteristics of international students from Latin America in Australia by comparative analysis of the overall student population. International student numbers from Latin America to Australia have reached unprecedented levels. A growing body of research exists on Latin American migrants in Australia and scholars such as Burges and Calderon have provided insightful analyses into educational trade relations between the two. Despite this, there still lacks a deeper understanding of the mobility characteristics of Latin American students, embedded within the scholarship of international migration broadly and international student mobility (ISM) specifically. In order to address this gap, the article interprets publicly available data in a growing segment of ISM research that understands mobility as an ongoing, processional and lifelong journey. This article therefore paints a picture of what we already know and what we still need to find out about Latin American students in Australia.